(untitled) (Islas, 2024)
Introduction: The work aims to systematize the theoretical foundations of the reading process for social transformation. Methods: The analytical-synthetic and inductive-deductive methods, the bibliographic review, were applied to systematize the concepts regarding the possibilities of reading for social transformation. Results: The conception of reading is resized that is not limited only to the school environment, but also to the study of the possibilities of adaptability of its essential postulates to phenomena that are results of the process of cultural democratization that has been witnessed in the world since the second half of the 20th century. Conclusions: Reading is a main tool to transform information into knowledge, it is at the base of lifelong learning and in the construction of a critical society, in the school, social and personal spheres.